Showcasing the Governance Assessment Tool as an “effective” contextual approach to water governance - Casiano Flores, Cesar; Mirnezami, Jalal; Bressers, Hans (Center for Risk Management & Sustainability and RSF Press, 2025)
Addressing water challenges requires policies tailored to their governance context. The lack of such consideration is among the reasons why decentralisation, privatisation, and integrated water resources management have not achieved their intended outcomes. The Governance Assessment Tool (GAT) helps improve the effectiveness of water policies. GAT assesses how effective the implementation of water policies is and helps to develop policy recommendations to improve the effectiveness of the policy. As the purpose of this paper is to showcase the capabilities of GAT, we present its application in two different governance contexts (Iran and Mexico) to the European one where GAT was created. In our case selection, we focus on different challenges in water services (water supply and sanitation). In Iran, it is a single case study that assesses the groundwater policy, and in Mexico, it is a comparative case study of three sub-basins where the wastewater treatment plant policy is assessed. For each case, the results provide insights for improving policy effectiveness, such as the need for farmer participation in Iran and the need to enhance coordination by subnational governments in Mexico. These results showcase the GAT capability to assessing in-depth single case studies (Iran) and comparative analysis (Mexico). Moreover, GAT allows systematisation to navigate our understanding of complex challenges and provides a framework for academic and practitioners to understand the context and to propose tailored policies.